Implementasi Data Mining Untuk Menganalisis Pola Peminjaman Buku Perpustakaan Dengan Menggunakan Metode Apriori: Implementasi Data Mining - Tri Yuli Yanto; Febe Maedjaja; Sunneng Sandino Berutu (Infact: International Journal of Computers, 2023)
The library is a place where you can find the information andknowledge you need. Library space is a very important means oforganizing book loans because it not only creates space and thenfills it with collections, but also pays attention to how the layout ofthe books is arranged. Therefore, the data is analyzed in order tohelp recommend the layout of books and borrowers can find theappropriate books. To determine the suggestion of borrowedbooks, with the existence of play data can use the a priorialgorithm, a kind of association rule. The market basket analysismethod used by the a priori algorithm to establish associationsbetween various variables allows the system to further analyze andidentify trends related to borrowed books. Based on the results ofthe analysis that has been carried out, it is stated that this a priorialgorithm can be used to display recommendations betweenborrowed books. The support value can show the classification ofbooks borrowed simultaneously while the confidence value canfind out the recommendations for books borrowed.